Kafka´s “In The Penal Colony” as a psychoanalytic figuration of the experience [Erfahrung] of acceptance [Annahme] - Barth, Luís Fernando Barnetche (Revista de Letras, 2015)
Based on Kafka’s (2011) “In the Penal Colony”, published in 1914, in which an unusual form of execution of criminals is described, where the accused – who ignores the grounds for his execution – is placed in a machine that inscribes the reason for his condemnation on his back, causing the condemned man’s death by transfixion, the aim of this paper is to investigate the psychological quality of the experience of limits. With the support of the original German-language text, the author examines the Kafkian attempt of the condemned to establish a true, revealing corporal experience through the “reading” of the sentence “inscribed” on his own body, by evoking the psychoanalytical concept of acceptance [Annahme] of unconscious content, through the liberation of psychological affection sparked by increased physical tension. This process is offered as a possible figuration of psychoanalytical experience [Erfahrung] of treatment, which, opposing itself to the idea of a mere existence, is understood as a profound experience that brings with it a learning experience that transforms into knowledge; an experience which goes beyond the subject and transforms it into the other. This work is based upon Freudian-Lacanian psychoanalytical literary criticism.